Construção e validação de protocolo gráfico para avaliação do cuidado seguro ao paciente renal crônico em hemodiálise - Paiva, Renilly de Melo (2021)
Safe and quality care in hemodialysis services aims to reduce or eliminate the occurrence of adverse events. This is because, it is an environment that presents several risk factors because it is an invasive and complex procedure. Thus, it is necessary to implement measures for patient safety in these services, as well as to identify problems and measure the quality of care and management. Thus, this study aimed to build and validate the content and appearance of a protocol for evaluating safe care in hemodialysis. It deals with a methodological study conducted by Pasquali's psychometric framework organized in three procedures, namely: theoretical procedures in which a Scoping Review was carried out to support the definition of the contents included in the protocol; empirical procedures construction of the protocol through scientific evidence and content and appearance validation via Google forms and Delphi steps with expert judges in the area of patient safety and kidney diseases; and, analytical procedures in which the analysis of the data from the previous phase was carried out using the content validation coefficient, items with a minimum agreement of 80% between judges were considered valid. The study is approved by the Ethics and Research Committee of the Federal University of Rio Grande do Norte, under Certificate of Ethical Appreciation No. 3,915,158 and CAAE: 29259020.7.0000.5537. After construction of the protocol, supported by the results of the Scoping Review, it was submitted to the appreciation of nine judges who responded to all stages of Delphi I, who made suggestions for improvement and improvement. In the Delphi II stage, six judges participated, reaching a general content validity coefficient of 0.88 in the checklist, 0.88 for the structure, process and result protocol, already in the appearance validation for the Suitability Assessment of Materials criteria obtained 0.91 for checklist and structure protocol and 0.88 for process and result. It is concluded that the graphic protocol for the evaluation of safe care for patients on renal dialysis is considered valid in its content and appearance.